Evaluasi Dampak Program Pelatihan KepemimpinanTransformatif Terhadap Komitmen Organisasi Dan Kepuasan Kerja Karyawan - Ageng Samudera; Norman Diaz Brahmantio; Regal Galih Sabala; Sentot Imam Wahjono (Journal of Innovative and Creativity, 2025)
This study aims to analyze the impact of Training Programs and Transformational Leadership on Organizational Commitment and Employee Job Satisfaction. The background highlights the essential role of the transformational leadership style in motivating followers to go beyond self-interest for the organization's greater good, leading to higher Organizational Commitment and Job Satisfaction. The method employed is quantitative with a survey approach15151515. The population of the study consists of employees in a manufacturing sector company with an active labor union 16, with a sample of 100 respondents selected through purposive sampling17171717. Data was analyzed using multiple linear regression analysis with the model: $Y=a+b_1X_1+b_2X_2+e$18181818. The regression results indicate that Training Program ($X_1$) and Transformational Leadership ($X_2$) partially and simultaneously have a positive and significant influence on Organizational Commitment ($Y$)19. The Training Program coefficient is $0.48$ (significance $0.000$), and the Transformational Leadership coefficient is $0.36$ (significance $0.001$)20. The coefficient of determination ($R^2$) is $0.512$, which means $51.2%$ of the variation in Organizational Commitment is explained by these two independent variables21. The main conclusion is that the combination of effective Training Programs and support from a transformational leader creates a conducive work atmosphere, enhances the sense of security, and promotes the achievement of strong Organizational Commitment.